Economic and Legal Aspects of Entrepreneurial Development in the Republic of Kazakhstan - KANTUREEV, Mansour T.; TULESHOVA, Gulnara B.; AGYMBAY, Asylbek O.; MOSKVITIN, Andrey I.; ABDRASILOVA, Zaure S.; BIMENDIEVA, Leila A. (Journal of Advanced Research in Law and Economics, 2017)
Entrepreneurship is an initiative, independent profit-driven activity of individuals without establishing a legal person carried out in one’s own name and under someone’s financial responsibility. The entrepreneur can conduct any types of statute-permitted business activities from the moment of the state registration as an individual entrepreneur. Currently entrepreneurship is a fact of life in Kazakhstan, certainly, it suffers many problems, but today the state makes every effort to promote its development.
Keywords: entrepreneurship; law; regulations; economy; development; politics; strategy; business